2017
DOI: 10.1200/jco.2017.35.15_suppl.e18331
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab in the treatment of metastatic renal cell carcinoma: A cost-utility analysis.

Abstract: e18331 Background: Nivolumab was recently shown to improve overall survival (OS) and health-related quality of life compared to Everolimus in metastatic renal cell carcinoma (mRCC) patients previously treated with antiangiogenic therapies (CheckMate-025 trial). The aim of this study is to assess the cost-utility of Nivolumab versus Everolimus from the perspective of the Canadian publicly funded healthcare system. Methods: To evaluate the cost-utility of Nivolumab versus Everolimus, a Markov cohort model that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[28] As more new drugs were approved for second-line therapy of mRCC, BSC became less common in second-line settings and cost-effectiveness analyses were able to model clinical parameters from head-to-head trials, such as the AXIS (AXItinib vs. Sorafenib in advanced renal cell carcinoma) trial for axitinib vs. sorafenib [32] and the CheckMate 025 trial for nivolumab vs. everolimus. [33] Eight studies included both nivolumab and everolimus in the comparators [29][30][31][34][35][36][37][38] and these two drugs were directly compared in six. [29,31,[34][35][36]38].…”
Section: Cea: Mrcc 2nd Linementioning
confidence: 99%
See 2 more Smart Citations
“…[28] As more new drugs were approved for second-line therapy of mRCC, BSC became less common in second-line settings and cost-effectiveness analyses were able to model clinical parameters from head-to-head trials, such as the AXIS (AXItinib vs. Sorafenib in advanced renal cell carcinoma) trial for axitinib vs. sorafenib [32] and the CheckMate 025 trial for nivolumab vs. everolimus. [33] Eight studies included both nivolumab and everolimus in the comparators [29][30][31][34][35][36][37][38] and these two drugs were directly compared in six. [29,31,[34][35][36]38].…”
Section: Cea: Mrcc 2nd Linementioning
confidence: 99%
“…[33] Eight studies included both nivolumab and everolimus in the comparators [29][30][31][34][35][36][37][38] and these two drugs were directly compared in six. [29,31,[34][35][36]38]. Only two out of the six studies found nivolumab to be cost effective compared to everolimus.…”
Section: Cea: Mrcc 2nd Linementioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis have assessed the relationship between clinical and economic benefits of pembrolizumab, axitinib, nivolumab and ipilimumab, isolated or in combination for mRCC management, using traditional strategies such as costeffectiveness and cost-utility analyses 15,16,39,40 . In Brazil, the National Sanitary Agency (Agência Nacional de Vigilância Sanit aria -ANVISA) is responsible for registering new drugs, an exclusive task of the State that intervenes in the production-consumption relationship by establishing legal rules for granting this registration.…”
Section: Discussionmentioning
confidence: 99%